THE STUDENTS’ DIFFICULTIES IN PRACTICING ARABIC’S MAHARAH KALAM AT THE ARABIC LANGUAGE EDUCATION DEPARTMENT IAIN LANGSA - Isnaini Lubis; Zulkipli Lessy; Muhammad Nizar Hasan (Universitas Islam Negeri Mataram, 2022)
Mah?rah kal?m (speaking skill) is one of four language skills for learning Arabic, the other three skills being istima' (listening), qir?’ah (reading), and kit?bah (writing). When learning to speak Arabic, students deal with both linguistic and non-linguistic challenges. This study used the descriptive analytical method with a qualitative approach to explore barriers in acquiring Arabic mah?rah kal?m. The subjects of this study were college students majoring in Arabic language education at IAIN Langsa, in Aceh. By means of interviews and questionnaire, the study found that impediments to mah?rah kal?m mastery were lack of self-confidence, limitations of introductory vocabulary, poor knowledge of grammar (qaw?’id) and of composition (tar?kib), and discomfort felt by listeners when lacking in conversational understanding. There were non-linguistic factors among the students too: differences in educational background; majoring in Arabic but not as a first choice; a limited language practice environment; and some limitations of teaching methodology. Accordingly, to improve students’ speaking skill, lecturers should seek to develop students’ motivation, memory, and practicing of speaking, by rehearsing examples from texts and from typical situations. To overcome barriers, academic lecturers should create supportive bi’ah lughawiyah, mandatory Arabic-day programs, and the use of media, such as YouTube, to expose students to new mufradah and pattern practices (ushlub).